Utilization of Water Hyacinth (Eichhornia crassipes) in Diets on Growth and Survival Rate of River Carp (Leptobarbus hoevenii) - Nirwan Fadli Pulungan; Indra Suharman; Adelina ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted from 20 April 2015-14 July 2015. Thepurpose of this research was know the amount of water hyacinth in the diets ongrowth, feed afficiency and protein retention of river carp (Leptobarbus hoevenii).Five isonitrogenus (30% crude protein) experimental diets was formulated tocontain 0, 10, 20, 30 and 40% water hyacinth and 100, 90, 80, 70 and 60% soybenmeal (P0, P1, P2, P3 and P4, respectively. Completely randomized design (CRD)was used in this experiment. The results showed that a diet containing 40% waterhyacinth and 60% soyben meal (P4) support a good specific growth rate(1.0%/day) feed efficiency rate (22.23%) forage digestibility (54.95%) and proteinretention (24.54%). Survival rate of fish was high (98%). In this concluded that upto 60% soyben meal can be substituted with water hyacinth in the diets for rivercarp.Key word: Diet, growth, Leptobarbus hoevenii, substitution, water hyacinth